2019
DOI: 10.1016/j.jprocont.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A new animal model of insulin-glucose dynamics in the intraperitoneal space enhances closed-loop control performance

Abstract: Current artificial pancreas systems (AP) operate via subcutaneous (SC) glucose sensing and SC insulin delivery. Due to slow diffusion and transport dynamics across the interstitial space, even the most sophisticated control algorithms in on-body AP systems cannot react fast enough to maintain tight glycemic control under the effect of exogenous glucose disturbances caused by ingesting meals or performing physical activity. Recent efforts made towards the development of an implantable AP have explored the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…FFM, fat-free mass. (44,(70)(71)(72)(73) Surgical complications (74) Lessens severe hypoglycemia more than subcutaneous insulin to varying degrees (72)(73)(74) Insulin aggregation and catheter occlusion in intraperitoneal pumps (77) Tends to avoid weight gain (74) Rapid absorption to approximate first-phase insulin release and reduce postprandial hyperglycemia (75,76) Approximates insulin balance between portal and peripheral circulations (76) Oral insulin delivery Rapid absorption to approximate first-phase insulin release (78) Limited bioavailability (78) Approximates insulin balance between portal and peripheral circulations (78) Absorption affected by food in the gut (79) Increases patient burden Hepatopreferential insulin analogs and hepatic-directed vesicle insulin Pharmacodynamic characteristics approximate balance in insulin action between portal and peripheral circulations (80)(81)(82) Concern for potential hepatic toxicity (83) Tends to avoid weight gain (83) Generally lowers hyperglycemia more than conventional insulin ( 83 primarily drives insulin resistance in type 1 diabetes. On the other side, reducing insulin doses would seemingly exacerbate hyperglycemia, which could also worsen cardiovascular outcomes and aggravate microvascular complications (57,58).…”
Section: Iatrogenic Hyperinsulinemia Has a Much Greater Association With Insulin Resistance Than Hyperglycemia In Type 1 Diabetesmentioning
confidence: 99%
“…FFM, fat-free mass. (44,(70)(71)(72)(73) Surgical complications (74) Lessens severe hypoglycemia more than subcutaneous insulin to varying degrees (72)(73)(74) Insulin aggregation and catheter occlusion in intraperitoneal pumps (77) Tends to avoid weight gain (74) Rapid absorption to approximate first-phase insulin release and reduce postprandial hyperglycemia (75,76) Approximates insulin balance between portal and peripheral circulations (76) Oral insulin delivery Rapid absorption to approximate first-phase insulin release (78) Limited bioavailability (78) Approximates insulin balance between portal and peripheral circulations (78) Absorption affected by food in the gut (79) Increases patient burden Hepatopreferential insulin analogs and hepatic-directed vesicle insulin Pharmacodynamic characteristics approximate balance in insulin action between portal and peripheral circulations (80)(81)(82) Concern for potential hepatic toxicity (83) Tends to avoid weight gain (83) Generally lowers hyperglycemia more than conventional insulin ( 83 primarily drives insulin resistance in type 1 diabetes. On the other side, reducing insulin doses would seemingly exacerbate hyperglycemia, which could also worsen cardiovascular outcomes and aggravate microvascular complications (57,58).…”
Section: Iatrogenic Hyperinsulinemia Has a Much Greater Association With Insulin Resistance Than Hyperglycemia In Type 1 Diabetesmentioning
confidence: 99%
“…53 In silico experiments were conducted by Huyett et al 48 for interperitoneal (IP; deliver in or administer through the abdominal cavity or peritoneum) insulin delivery and IP glucose sensing (IP–IP), 20,54 for an implantable artificial pancreas. Chakrabarty et al 55 conducted the first in vivo experiment for IP–IP sensing in dogs using a canine model.…”
Section: Control Algorithmsmentioning
confidence: 99%
“…The purpose of this article is to present a relatively simple nonlinear model to approximate T1DM glucose dynamics when insulin and glucagon boluses are introduced in the intraperitoneal (IP) cavity. The conception of a new model is also motivated by the fact that most of the work developed for AP systems is adapted to subcutaneous insulin delivery [23].…”
Section: Introductionmentioning
confidence: 99%
“…A tight glycemic control is difficult to attain with an AP operating with subcutaneous insulin infusion, due to delays in insulin absorption and slow insulin-clearance rates [1], [23]. For these reasons, the intraperitoneal route to infuse insulin has been investigated, since insulin-glucose kinetics are significantly faster in the IP cavity than subcutaneously [23], [24]. Furthermore, it has been observed that blood glucose increases faster when glucagon is delivered in the IP cavity, compared with subcutaneous glucagon infusions [5].…”
Section: Introductionmentioning
confidence: 99%